Optimalisasi Edukasi Kesehatan Perilaku Hidup Sehat Siswa Di SMP Negeri 7 Lhokseumawe - Dewi, Risna; Syafridah, Anita; Maisyura, Maisyura; Zawi, Rizam; Ramadhana, Muhammad Indra (Universitas Malikussaleh, 2025)
This community service program aims to optimize health education and the implementation of healthy living behaviors at SMP Negeri 7 Lhokseumawe through a structured public administration approach. The main challenges addressed include a lack of awareness among students and parents about the importance of healthy living, limited health-supporting facilities at the school, and low collaboration between the school and external partners. The proposed solutions include education and training on healthy living behaviors, regular health check-ups, strengthening parental involvement, and developing a monitoring and evaluation system based on success indicators. The methods employed involve a participatory approach, multisectoral collaboration, and practice-based education. The expected outcomes of this program are increased awareness among students and parents about healthy living behaviors, the availability of adequate health-supporting facilities at the school, and the establishment of better collaboration patterns between the school and external parties. With this integrated approach, the program is expected to create a healthier school environment and support the holistic development of students.